Uji Efektivitas Antiinflamasi Ekstrak Etanol dan Fraksi Daun Ciplukan (Physalis angulata L.) Terhadap Mencit Putih Jantan (Mus musculus) - Listina, Osie (Usadha, 2024)
Inflammation is a local protective response caused by tissue damage. Antiinflammatory drugs steroids and non steroids have many side effects so that there are many antiinflammatory development derived from natural materials, especially in plants.This study aimed to determine the anti-inflammatory effects of ethanol extract, N-hexane fraction and ethyl acetate fraction with doses of 600mg/kgBW, 1200mg/kgBW and 1800mg/kgBW. The method used was the production of udem induced with 1% carragenin subplantar. The study was conducted by administering carragenine as an inflammatory mediator on the feet of mice, then administering orally suspension Ethanol extract, N-hexane fraction and ethyl acetate fraction. Sodium CMC was as a negative control and diclofenac sodium was as a positive control. Measurements were taken every 30 minutes for 6 hours after induction of 1% carragenin. Based on the result of research, ethanol extract with dose of 600mg/kgBB had anti-inflammatory power of 48,43%, N-hexane fraction with dose 1200mg/kgBB had antiinflammatory power of 33,21% and ethyl acetate fraction with dose 1800mg/kgBB had anti inflammatory power equal to 50,08% and the most effective dose of anti inflammatory power of ethanol extract and ciplukan leaf fractionation at fraction of ethyl acetate 1800mg / kgBB with anti inflammatory value of 50,08%.